Exploring istighfar as an emotive and religious interjection in Indonesian - Afrizal, Mohamad; Mijianti, Yerry; Anggraeni, Astri Widyaruli (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
Istighfar is an interjection in the Indonesian, borrowed from Arabic and widely used in various social situations, both in personal and public spheres. As a religious interjection that holds a significant position in the linguistic practices of Muslim communities, istighfar reflects both emotional responses and moral awareness toward events perceived as negative or sinful. This study aims identified the characteristics of istighfar as an interjection and to analyze its meaning using the Natural Semantic Metalanguage (NSM) approach. Employing a qualitative-descriptive method, the primary data were drawn from fifteen Indonesian novels by prominent authors, while supplementary data were taken from online news headlines and everyday communicative experiences, including spontaneous conversations and selected social media comments within the researcher’s observation. The analysis proceeded in two stages: categorizing istighfar within interjection typology and constructing semantic explications using NSM. The results show that istighfar fulfills nearly all prototypical features of interjections and carries complex spiritual content. Its use not only reflects emotional expression but also constructs and represents the speaker’s religious identity. This research affirms that language can reflect levels of religiosity, as demonstrated by the frequent use of religious interjections in Indonesian society, which is known for its high level of religious devotion.